Stones from a Glasshouse: The Paradoxical Condemnation of Reading Recovery in the Ontario Human Rights Commission Right to Read Report - Stouffer, Joe; Van Dyke, Janice (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2023)
The Ontario Human Rights Commission’s (OHCR) Right to Read Report calls for school districts to implement early literacy interventions that have been scientifically proven to be effective for young children with reading difficulties. The acknowledgment of early intervention as an essential service for young children experiencing reading difficulties is a strong and welcome message in the report. However, the report recommends a narrow course for reading interventions in Ontario, drawing on discourse from the Science of Reading community, which questionably frames current interventions, such as Reading Recovery, as unscientific, ineffective commercial programs. In this response, the authors contest the one-sidedness of these recommendations based on a paradox in the report between what constitutes an effective early literacy intervention supported by science and the standards for effectiveness the OHRC requires of interventions it endorses versus those it discredits. Rather than dismissing one approach or the other outright, a call is made for school leadership to consider broader reading science and the strengths of various approaches instead of narrowing the menu of effective literacy interventions that may support diverse learners.